2004
DOI: 10.1182/blood.v104.11.1489.1489
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of First-Line Thalidomide-Dexamethasone over Vincristine-Doxorubicin-Dexamethasone in Preparation for Autologous Stem Cell Transplantation for Multiple Myeloma.

Abstract: The aim of the present study was to compare thalidomide-dexamethasone (THAL-DEX) and vincristine-doxorubicin-dexamethasone (VAD) as primary therapy for newly diagnosed multiple myeloma (MM). For this purpose, we performed a retrospective matched case-control analysis of 200 patients who were treated with THAL-DEX (n=100) or VAD (n=100) on two consecutive studies from 1996 to 2003. Thalidomide was given orally at the daily dose of 200 mg, while VAD was administered by continuous infusion. Pulsed dexamethasone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 0 publications
1
45
0
1
Order By: Relevance
“…These data are not unexpected, as dexamethasone is known to suppress osteoblastogenesis, to induce osteoblast apoptosis, and to downregulate osteoprotegerin, thus allowing the interaction of receptor activator of NFkB ligand (RANK‐L), with its own receptor, RANK, that is subsequently activated and promotes the proliferation of pre‐osteoclasts, and activation of mature osteoclasts (33). Dexamethasone, however, is highly effective in MM, and shows a synergistic activity in combination with thalidomide, ultimately resulting in 40–50% partial response rates in pre‐treated patients (8, 34) and 65–75% responses in patients with newly diagnosed MM (9–11). Little is known about the effects of thalidomide on cells implicated in bone metabolism as osteoblasts or osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are not unexpected, as dexamethasone is known to suppress osteoblastogenesis, to induce osteoblast apoptosis, and to downregulate osteoprotegerin, thus allowing the interaction of receptor activator of NFkB ligand (RANK‐L), with its own receptor, RANK, that is subsequently activated and promotes the proliferation of pre‐osteoclasts, and activation of mature osteoclasts (33). Dexamethasone, however, is highly effective in MM, and shows a synergistic activity in combination with thalidomide, ultimately resulting in 40–50% partial response rates in pre‐treated patients (8, 34) and 65–75% responses in patients with newly diagnosed MM (9–11). Little is known about the effects of thalidomide on cells implicated in bone metabolism as osteoblasts or osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of the patients was 53.5 yr (range 34–65), and none of them had abnormal renal function or hypercalcaemia. After informed consent, patients were enrolled in the ‘Bologna 2002’ clinical trial (11). Consequently, they received 4 months of combined oral thalidomide (100 mg/d for 2 wk and 200 mg/d thereafter) and dexamethasone (40 mg/d on days 1–4, 9–11, 17–20/28 on odd cycles and on days 1–4 on even cycles) as remission induction treatment prior to peripheral blood stem cell collection and subsequent double autologous transplant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of VTE was 10% without a significant increase in the incidence of bleeding complications [102]. In contrast to the experience of Weber and colleagues and Zangari et al with 1.0 mg of warfarin [53,101], Cavo et al and Ikhlaque et al reported that fixed, low-dose warfarin (1.25 mg/d or 1-2 mg) resulted in effective thromboprophylaxis for newly diagnosed patients treated with thalidomide and dexamethasone [103,104]. It is controversial whether this dose of warfarin can be safely used without the added burden to the patient of INR monitoring.…”
Section: Prophylaxis Of Hemostatic Complicationsmentioning
confidence: 96%
“…However, VAD have several disadvantages including the need for an intravenous indwelling catheter, which predisposes patients to catheter related sepsis and thrombosis; most of the activity of VAD was from high‐dose dexamethasone component (5). Recently the combination of thalidomide plus dexamethasone (Thal/Dex) has emerged as an alternative to VAD in newly diagnosed MM patients based on three phase II clinical trials and one case–control study (6–9). Response rates with Thal/Dex varied from 64% to 76%, which are comparable or better than those obtained with VAD (9, 10).…”
mentioning
confidence: 99%